Studi Timbulan Dan Komposisi Sampah Sebagai Dasar Perencanaan Sistem Pengelolaan Sampah Di Kampus Bina Widya Universitas Riau - Sri Febria; Lita Darmayanti; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
In all activities, human will produce a residual in a form of solid called solid waste. Kampus Bina Widya is a one of university in Pekanbaru with all of its activities is not hampered from solid waste productiom and problems coming from it, one of which can be seen on the amounts of solid waste in LPS (Land Disposal meantime) located behind of a Stadion Mini. This study aims to determine the waste generation and composition at Kampus Bina Widya and planned waste management system that includes lug, collection, transportation and the planned dump site (TPST) in Kampus Bina Widya, so the landfill activity on campus no longer exists. This study begins with the generation and waste composition studies conducted in 4 faculty, 3 offices, roads, public housing, hospitals and mosques.The study results showed the composition and in 2014 the daily waste generation of 9.448 l/day with composition is inorganic waste by 50,55% % and organic waste by 49,45%. Waste management planning in Campus Bina Widya include disaggregated lug to lug needs a capacity of 10 l bin for organic waste as much as 325 units and as many as 514 units of inorganic waste, bin capacity of 30 l to 108 units as much organic waste and inorganic waste as much as 171 units, bin capacity 60 l for organic waste as much as 62 units and 88 units of inorganic waste. Collection system in the form of segregated polling stations with a capacity of 4 m3 tub. A transport fleet capacity of 4 m3 pick up 2 units. The area of land needs TPSTs in Bina Widya Campus is an area of 635.33 m².Keywords: generation and waste composition, waste management systems, TPST